After Rescue: Evaluation of Strategies to Stabilize and Integrate Adult Survivors of Human Trafficking to the United States, 2006-2011 - Gozdziak, Elzbieta M. ([Verlag nicht ermittelbar], 2023)
This mixed-methods project examined comprehensive case management services provided from fiscal years 2006 to 2011 to adult survivors of human trafficking born outside of the United States. The purpose was to evaluate the effectiveness of different intervention strategies to stabilize, rehabilitate, and integrate survivors into wider society. Case management services were funded by the Anti-Trafficking in Persons (ATIP) Program of the Office of Refugee Resettlement (ORR) under the Per Capita Reimbursement Contract administered by the U.S. Conference of Catholic Bishops (USCCB). Several data sources were used for analysis: 1) A longitudinal, relational database of survivor cases as reported electronically by subcontracted social service providers throughout the United States, 2) intake assessment and case notes, and 3) group discussions and in-depth interviews with service providers to gain an understanding of the processes and dynamics involved in protecting survivors from repeat victimization and facilitating their reintegration into the mainstream society. Two datasets are included in this collection: the Base dataset (DS1), a cleaned and merged version of USCCB records, and the Analysis dataset (DS2), which includes all base items and variables constructed for analysis. The qualitative interview data will be made available at a future date.